2006
DOI: 10.1111/j.1469-0691.2006.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific and sensitive diagnosis of syphilis using a real-time PCR for Treponema pallidum

Abstract: A real-time PCR assay with a Taqman probe was developed that targeted the polA gene of Treponema pallidum. The test was validated using an analytical panel (n = 140) and a clinical panel of genital samples (n = 112) from patients attending a sexually transmitted infections clinic. High sensitivities and specificities of 94-100% were achieved using two real-time PCR platforms, the Rotor-Gene and the iCycler. The assay can be completed within 2 h, enabling reporting in <8 h. This fast and robust assay is suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 11 publications
4
36
0
2
Order By: Relevance
“…The advantages of a real-time PCR are the ability to detect the pathogen directly, the short turnaround time, and the ease of performance. We previously developed a real-time PCR that targets the polA gene and that is performed with swabs from the (ano)genital ulceration(s) (10).…”
mentioning
confidence: 99%
“…The advantages of a real-time PCR are the ability to detect the pathogen directly, the short turnaround time, and the ease of performance. We previously developed a real-time PCR that targets the polA gene and that is performed with swabs from the (ano)genital ulceration(s) (10).…”
mentioning
confidence: 99%
“…pallidum polA gene (TP0105) has been widely used as a target for detection of the syphilis agent according to the protocols of Liu et al (204) and Behrhorf et al (214). Several examples of quantitative amplification tests targeting polA are also available (215)(216)(217)). An alternative approach to DNA detection was proposed in 1997 by Centurion-Lara et al, who developed a reverse transcriptase PCR (RT-PCR) assay followed by probe hybridization to detect T. pallidum subsp.…”
Section: Direct Detection Methodsmentioning
confidence: 99%
“…Another study found positivity ratio of 39.1% for ttp47 PCR (260 bp) and 31.1% for polA PCR (378 bp), in blood samples from patients with latent syphilis (Castro et al, 2007). The real-time PCR had been developed for detection of T.pallidum DNA in clinical samples, they targeted polA gene (Heymans et al, 2010;Koek et al, 2006;Leslie et al, 2007) or tpp47 gene (Gayet-Ageron et al, 2009). The first test was validated using an analytical panel (n = 140) and a clinical panel of genital samples (n = 112) from patients attending a sexually transmitted infections clinic.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…The first test was validated using an analytical panel (n = 140) and a clinical panel of genital samples (n = 112) from patients attending a sexually transmitted infections clinic. High sensitivities and specificities of 94-100% were achieved using two real-time PCR platforms, the Rotor-Gene and the iCycler (Koek et al, 2006). Leslie et al developed real-time PCR which analytical sensitivity was estimated to be 1.75 target copies per reaction.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%